2012
DOI: 10.1080/17452759.2012.668701
|View full text |Cite
|
Sign up to set email alerts
|

A combined additive layer manufacturing / indirect replication method to prototype 3D vascular-like structures of soft tissue and endocrine organs

Abstract: 2012) A combined additive layer manufacturing / indirect replication method to prototype 3D vascular-like structures of soft tissue and endocrine organs, Virtual and Physical Prototyping, 7:1, 3-11,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…As we have previously tested in a number of organ's model, 25,26,[71][72][73][74] we perfused the scapular vascular pedicles with a solution of thermoplastic material, the biocompatible polylevolactic acid (PLLA). 28 Then, based on an hoc developed modification of a phase dark-field contrast light microscopic technique, 30 we observed a striking birefringence of the polymerized PLLA lining blood vessel walls in the decellularized cortical compartment, as expected for the crystalline structure of this polymer.…”
Section: Cell Compatibility Of the 3d Scapular Organoidmentioning
confidence: 99%
“…As we have previously tested in a number of organ's model, 25,26,[71][72][73][74] we perfused the scapular vascular pedicles with a solution of thermoplastic material, the biocompatible polylevolactic acid (PLLA). 28 Then, based on an hoc developed modification of a phase dark-field contrast light microscopic technique, 30 we observed a striking birefringence of the polymerized PLLA lining blood vessel walls in the decellularized cortical compartment, as expected for the crystalline structure of this polymer.…”
Section: Cell Compatibility Of the 3d Scapular Organoidmentioning
confidence: 99%
“…After the master vascular tree had been coated with a metallic shield and emptied by thermal dissolution, the resulting vascular spaces were prepared for eventual refi lling with PCL and PLLA under vacuum conditions, in order to obtain an accurate biocompatible replica of the 3D vessel geometry. Finally, the copper shield was deoxidized with ammonia, and electrolyzed by current fl ow reversal at specifi c frequency (Bassoli et al , 2012b). Similar procedures are being investigated for the replication of the intraglandular arterial network of the adult human thyroid with biomaterials.…”
Section: Studies On the Fabrication Of Vascular-like Reticular Scaffoldsmentioning
confidence: 99%
“…The results showed that this method had advantages over other rebuilding methods in terms of accuracy, speed, safety and cost. E. Bassoli et al, 17 reported a combined 3D printing/indirect replication method to fabricate 3D vascular-like structures of soft tissue 17 ; using the ProJet® HD 3000 3D printer from 3D Systems Inc. to print the negative mold of the vascular structure.…”
mentioning
confidence: 99%